Purification and characterization of cold-adapted and salt-tolerant dextranase from Cellulosimicrobium sp. THN1 and its potential application for treatment of dental plaque - Xu, Linxiang; Zhang, Yan; Liu, Nannan; Wei, Zhen; Wang, Zhen; Wang, Yonghua; Wang, Shujun (Frontiers in Microbiology, 2022)
The cold-adapted and/or salt-tolerant enzymes from marine microorganisms were confirmed to be meritorious tools to enhance the efficiency of biocatalysis in industrial biotechnology. We purified and characterized a dextranase CeDex from the marine bacterium Cellulosimicrobium sp. THN1. CeDex acted in alkaline pHs (7.5-8.5) and a broad temperature range (10–50 °C) with sufficient pH stability and thermostability. Remarkably, CeDex retained approximately 40% of its maximal activities at 4 ℃ and increased its activity to 150% in 4 M NaCl, displaying prominently cold adaptation and salt tolerance. Moreover, CeDex was greatly stimulated by Mg2+, Na+, Ba2+, Ca2+ and Sr2+, and sugarcane juice always contains K+, Ca2+, Mg2+ and Na+, so CeDex will be suitable for removing dextran in the sugar industry. The main hydrolysate of CeDex was isomaltotriose, accompanied by isomaltotetraose, long-chain IOMs, and a small amount of isomaltose. The amino acid sequence of CeDex was identified from the THN1 genomic sequence by Nano LC-MS/MS and classified into the GH49 family. Notably, CeDex could prevent the formation of Streptococcus mutans biofilm and disassemble existing biofilms at 10 U/mL concentration and would have great potential to defeat biofilm-related dental caries.